GP163 Improving patient experience through the use of a short stay observation unit in a pediatric hospital, a pilot study. (June 2019) - Fagan, Claire; Ryan, Sharon; Fitzgerald, Elaine; McNamara, Roisin; Fitzpatrick, Patrick; Okafor, Ike; Flynn, Helen; Broderick, Joan; Kandamany, Nandini
Abstract : The Emergency Department (ED) at Children's University Hospital, Temple Street is constantly running at maximum capacity due to limited space and in-patient beds, as well as inadequate staffing. This leads to a number of issues including: reduced patient flow, department overcrowding, unacceptable patient experience times and possible adverse events. A short stay observation unit (SSOU) was introduced to improve flow and patient experience. The RCPCH (2017) have defined a short stay unit as a 'dedicated facility providing assessment, observation and treatment of an illness, without the need for inpatient admission and can be a safe and efficient way of managing their care.' Our aim was to utilize beds in a different way to improve patient safety and patient flow in the ED, therefore improving PET times and patient satisfaction. We developed a local implementation group that met weekly to progress and change as necessary. We developed set admission criteria and standard operating procedures for the department. Weekly audits for patient length of stay in the SSOU, ED trolley wait times monitored weekly, parent and staff satisfaction surveys, PET times monitored weekly. Over the duration of the 8 week pilot study; Average length of stay in the SSOU was 11.7 hours 164 patients through the SSOU in 8 weeks, at 1.2 patients per available bed/day Trolley wait times have dropped to the previous 2 years Satisfaction surveys showed that the SSOU positively affected patients hospital experience and the ED staffs workload The utilisation of beds and resources in a different way can have a positive impact on patient care. Parent satisfaction and patient flow can be greatly improved from implementing a permanent SSOU. The ED can be used more efficiently and patient safety improved through effective use of resources. Welcomed changes can have a big impact on staff morale. We recommend that for future use, the SSOU be run as a standalone unit by the ED staff on a daily basis for the entirety of its opening hours. The SSOU should be in operation for at minimum the busy winter period, that being from late September to early May.